Tunable doping of graphene by using physisorbed self-assembled networks. Issue 48 (24th November 2016) - Phillipson, Roald; Lockhart de la Rosa, César J.; Teyssandier, Joan; Walke, Peter; Waghray, Deepali; Fujita, Yasuhiko; Adisoejoso, Jinne; Mali, Kunal S.; Asselberghs, Inge; Huyghebaert, Cedric; Uji-i, Hiroshi; De Gendt, Stefan; et al.
Abstract : A strategy for tuning the Fermi level of graphene based on controlling the density of doping moieties in self-assembled networks. Abstract : One current key challenge in graphene research is to tune its charge carrier concentration, i.e., p- and n-type doping of graphene. An attractive approach in this respect is offered by controlled doping via well-ordered self-assembled networks physisorbed on the graphene surface. We report on tunable n-type doping of graphene using self-assembled networks of alkyl-amines that have varying chain lengths. The doping magnitude is modulated by controlling the density of the strong n-type doping amine groups on the surface. As revealed by scanning tunneling and atomic force microscopy, this density is governed by the length of the alkyl chain which acts as a spacer within the self-assembled network. The modulation of the doping magnitude depending on the chain length was demonstrated using Raman spectroscopy and electrical measurements on graphene field effect devices. This supramolecular functionalization approach offers new possibilities for controlling the properties of graphene and other two-dimensional materials at the nanoscale.